2014
DOI: 10.1111/aor.12379
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Renal Function and Extracorporeal Membrane Oxygenation Use: A Single-Center Experience

Abstract: The effects of extracorporeal membrane oxygenation (ECMO) support on renal function in children with critical illness are unknown. The objective of this study was to investigate the impact of ECMO on renal function among children in different age groups. We performed a single-center retrospective observational study in critically ill children ≤ 18 years supported on ECMO for refractory cardiac or pulmonary failure (2006-2012). The patient population was divided into four age groups for the purpose of compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 14 publications
(16 reference statements)
3
9
1
Order By: Relevance
“…On the basis of our study, the ECMO duration was longer in the ARF group than that in the non‐ARF group, which supports the result of Gupta et al . Long duration of ECMO support was a risk factor of ARF in pediatric cardiac patients during ECMO .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…On the basis of our study, the ECMO duration was longer in the ARF group than that in the non‐ARF group, which supports the result of Gupta et al . Long duration of ECMO support was a risk factor of ARF in pediatric cardiac patients during ECMO .…”
Section: Discussionsupporting
confidence: 90%
“…This study manifested that the incidence of ARF was 40.5% in pediatric patients after cardiac surgery requiring ECMO support. This result was higher than that in other reports (16–37%) . Open cardiac surgery leads to acute kidney injury (49.9%) .…”
Section: Discussioncontrasting
confidence: 60%
“…(6, 13, 2123) Although timing of injuries is not reported to ELSO, Gupta found that renal function commonly improved after ECMO initiation suggesting most acute kidney injury occurs prior to ECMO. (24)…”
Section: Discussionmentioning
confidence: 99%
“…34 Limited metabolism also occurs in the liver by arylsulfatase and catechol-O-methyltransferase into metabolites with little or no antifungal activity. 15 While the impact of ECMO on renal dysfunction is well described, 35 the effect of ECMO on hepatic transporters and metabolic capacity is unknown. Micafungin PK studies in adults with severe hepatic dysfunction, revealed lower micafungin exposure and higher CL compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%